Activating the "Big Man": Social Status, Patronage Networks, and Pro-Social Behavior in African Bureaucracies. (20th February 2022) - Harris, Adam S; Meyer-Sahling, Jan-Hinrik; Mikkelsen, Kim Sass; Schuster, Christian
Abstract: Public service delivery by African states is often characterized as particularist, favoring ethnic, personal or political networks of those inside the state over universalist, pro-social services to citizens. One explanation for particularist service delivery focuses on societal patronage norms, with "Big Men" providing for members of their networks. Despite the prominence of this line of reasoning and the anecdotal prevalence of "Big Men" in politics and society, hardly any research has quantitatively assessed the effects of "big man" governance inside the state. Through a behavioral experiment with over 1, 300 Ugandan bureaucrats, our article seeks to address this gap. In the experiment, we find that activating social status—that is, "big man" status—in bureaucrats embedded in patronage networks significantly curbs their pro-social behavior. Our article contributes an important empirical micro-foundation to help explain one cause of limited universal service delivery by bureaucrats.